2021
DOI: 10.5194/gmd-2021-301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GSTools v1.3: A toolbox for geostatistical modelling in Python

Abstract: Abstract. Geostatistics as a subfield of statistics accounts for the spatial correlations encountered in many applications of e.g. Earth Sciences. Valuable information can be extracted from these correlations, also helping to address the often encountered burden of data scarcity. Despite the value of additional data, the use of geostatistics still falls short of its potential. This problem is often connected to the lack of user-friendly software hampering the use and application of geostatistics. We therefore … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…These nine 2D velocity models (Figure 3a) are used to estimate the 3D velocity distribution in the subsurface of the catchment with the ordinary Kriging (e.g., Bourges et al, 2012). We used the GSTools toolbox (Müller et al, 2021) and followed the procedures proposed by Flinchum et al (2018) to construct the 3D velocity model. One advantage of using GSTools is that the topography can be kept during the Kriging such that estimated velocities near the ground surface have low uncertainties.…”
Section: D Seismic Velocity Modelmentioning
confidence: 99%
“…These nine 2D velocity models (Figure 3a) are used to estimate the 3D velocity distribution in the subsurface of the catchment with the ordinary Kriging (e.g., Bourges et al, 2012). We used the GSTools toolbox (Müller et al, 2021) and followed the procedures proposed by Flinchum et al (2018) to construct the 3D velocity model. One advantage of using GSTools is that the topography can be kept during the Kriging such that estimated velocities near the ground surface have low uncertainties.…”
Section: D Seismic Velocity Modelmentioning
confidence: 99%
“…Contaminant transport at field scale is strongly impacted by the heterogeneity of the subsurface. In this work we considered a cross section of a heterogeneous aquifer with a spatially variable distribution of the hydraulic conductivity created with the open-source software package GSTools (Müller et al, 2022;Müller & Schüler, 2021) using the values and statistics reported for the well-characterized Borden field site. An exponential covariance model was adopted, with average hydraulic conductivity K = 7.17 × 10 −5 m s −1 , variance ln K = 0.29, and correlation length in x and z direction I x and I z of 2.8 and 0.12 m, respectively (Sudicky, 1986).…”
Section: Field-scale Setupmentioning
confidence: 99%
“…For the specific case of kriging, a third interface exports the variogram directly into a gstools kriging class instance. At the time of writing, available kriging algorithms were simple kriging, ordinary kriging, universal or regression kriging, kriging with external drift and kriging the mean (Müller et al, 2021).…”
Section: Scikit-gstat and Gstoolsmentioning
confidence: 99%
“…A multitude of Python packages that were related to geostatistics could be found. A popular geostatistics-related Python package is pykrige (Murphy et al, 2021). As the name already implies, it is mainly intended for kriging interpolation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation